Hieracium oycoviense (Asteraceae), a new pentaploid species in H. sect. Grovesiana from Poland - Szeląg, Zbigniew (Phytotaxa, 2026)
Hieracium oycoviense is a new apomictic, pentaploid (x = 9) species combining the morphological features of Scandinavian H. oistophyllum and an unrecognised taxon of the sub-Mediterranean H. racemosum aggregate. It grows in a calcareous slope in the Ojców National Park in southern Poland.